The Role of Hypertension and Obesity in the Pathogenesis and Progression of Ischemic Heart Disease. A Clinical and Epidemiological Perspectives - Gohar Ali, Ghulam Hussain, Muhammad Tahir, Huzaifa Nazir Siddiqui, Aamena Gardazi, Shahid Mukhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertension and obesity are major contributors to ischemic heart disease (IHD), a leading cause of global morbidity and mortality. Both conditions independently and synergistically accelerate cardiovascular damage through mechanisms such as endothelial dysfunction, arterial stiffness, and systemic inflammation. While their individual roles are well-established, their combined impact on IHD progression in high-burden populations, such as in Pakistan, requires further investigation. Aims and Objectives: This study aimed to evaluate the prevalence of hypertension and obesity among IHD patients, identify associated clinical and biochemical risk factors, and assess the contribution of lifestyle behaviors to disease progression. The goal was to provide evidence-based insights for targeted interventions. Methodology: A cross-sectional observational study was conducted on 200 participants (aged 30–75 years) with confirmed IHD at Nishtar Hospital, Multan, Pakistan (February 2022-December 2022). Data were collected through structured interviews, medical records, anthropometric measurements, and biochemical investigations. Statistical analyses included chi-square tests, t-tests, and ANOVA, with significance set at p < 0.05. Results: This cross-sectional study included 200 participants (mean age 55.3 ± 10.4 years, 58.5% males). Hypertension was prevalent in 74%, with mean systolic and diastolic pressures of 142.7 ± 16.5 mmHg and 89.3 ± 12.2 mmHg, respectively (p < 0.001). Obesity affected 62% of participants, with central obesity in 71.2% (p < 0.01). Elevated total cholesterol (65%), LDL cholesterol (73%), and hs-CRP (64%) (p < 0.001) were observed. Behavioral risks included high sodium intake (75%), sedentary lifestyle (48%), and smoking (34% active, 28% former). These findings demonstrate the synergistic role of hypertension and obesity in exacerbating IHD progression. Conclusion: Hypertension and obesity significantly contribute to IHD pathogenesis. Integrated clinical management and public health initiatives targeting these conditions through lifestyle and dietary modifications are critical. Future research should focus on personalized approaches and long-term outcomes to reduce IHD burden. Keywords: Hypertension, Obesity, Ischemic Heart Disease, Cardiovascular Risk, Public Health, Lifestyle Modification.